Strategy Development of Red Ginger-Cinnamon Coffee of Tanah Wulan Village, Indonesia - Dyah Ayu Savitri; Gatot Subroto; Noer Novijanto; Tsania Afifatus Zahro (Journal La Bisecoman, 2022)
Coffee is one of the Indonesia's leading plantation commodities. Nowadays there is much interest to use the mixture of spices and herbs to add the characteristics of the taste and effects or efficacy of the brewed coffee. Spice coffee is a roasted coffee product that is added to a mixture of spices and brewed using hot water. One of the producer of spices coffee in Bondowoso district, Indonesia is a woman farmer group of Tanahwulan village. The product is manufactured by using various mixture of spices such as red ginger and cinnamon. This study aims to assess the financial feasibility of the red ginger and cinnamon coffee business and its development strategy so that these products are highly competitive as a quality Indonesian agro-industrial product. This research was a quantitative descriptive study using primary and secondary data. Primary data obtained by observations and questionnaires. Meanwhile, secondary data were obtained from various literatures. The data analysis methods used were financial feasibility analysis and SWOT analysis. The business financial analysis results explained that the business of Red Ginger-Cinnamon Coffee of Tanah wulan village was feasible to be executed. Based on the sensitivity analysis, the business could still exist if the second scenario applied with scenario of 5% increase in raw materials and 3% decrease in selling prices. Based on SWOT Analysis, the business is in the most profitable situation. Therefore, it is necessary to apply the aggressive strategy by taking advantage of existing opportunities and internal strengths of the organization.